Contact with the baby following stillbirth and parental mental health and well-being: a systematic review. Issue 11 (27th November 2015) - Hennegan, Julie M; Henderson, Jane; Redshaw, Maggie
Abstract : Objective: To collate and critically appraise extant evidence for the impact of contact with the stillborn infant on parental mental health, well-being and satisfaction. Design: Systematic review. Data sources: A structured systematic search was conducted in 13 databases, complemented by hand-searching. Study eligibility criteria: English language studies providing quantitative comparison of outcomes for parents who held their baby or engaged in other memory-making activities, such as having photos and handprints, compared to those who did not, were eligible for inclusion. Outcome measures: Primary outcomes included clinically diagnosed mental health issues, standardised assessment of mental health issues or self-reported psychological distress. Secondary outcomes included poor health, relationship difficulties and satisfaction with the decision to have contact with the baby. Results: Two authors independently screened abstracts, selected potentially eligible studies, extracted data and evaluated the quality of included papers. 11 eligible studies, reported in 18 papers, were included. Studies were heterogeneous, precluding quantitative synthesis, thus a narrative synthesis is presented. Studies presented high risks of bias, particularly in regard to sample representativeness, and confounder identification and adjustment. Results were mixed concerning the impact of holding the stillborn baby on mental health and well-being. One study found no significant effects, and two studies reported no impact on depression. Conflicting effects were found for anxiety and post-traumatic stress. Other memory-making activities were not found to have a significant association with mental health or well-being outcomes. Across studies, mothers were satisfied with their decision to hold their baby or engage in other memory making. Conclusions: Evidence for the impact of holding the stillborn baby on mental health and well-being is sparse, and of poor quality. High-quality research guided by a priori hypotheses, with attention to potential confounders and moderating effects, is needed to provide more rigorous evidence to guide practitioners' and parents' decision-making for care following stillbirth. Review protocol number: PROSPERO CRD42014013890.